Tingkat Efektivitas Pelaksanaan Program Pemberdayaan Ekonomi Masyarakat Pesisir (Pemp) - Sukmawati Abdullah; Awaluddin Hamzah; Dwi Yudha Prabowo (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2021)
The purpose of this study is to analyze the level of effectiveness of the Coastal Community Economic Empowerment (PEMP) program in Abeli District. The research location was determined by purposive sampling, with the consideration that Abeli District is a coastal area in Kendari City which is the target of the PEMP program. Methods of data analysis using qualitative descriptive methods, using criteria to determine the level of effectiveness of the empowerment program. The results of the analysis based on the criteria used show that the mentoring activities are said to be quite effective, the mentoring activities are said to be effective, the formation of the LEPP-M3 institution and the distribution of aid funds are said to be very effective.